O processo ensino aprendizagem de Física em turmas do ensino médio que possuem alunos com deficiência intelectual - Silva, Pedro Paulo Santos da (2016)
The purpose of this research was to propose a teaching methodology for implementation in the teach-and-learn process of Physics that attends students with Intellectual Disabilities (ID) and contributes to the process of inclusion at school. It was structured around the search for answers to the following research problem: What are the characteristics that a teaching methodology needs had to contribute effectively to the teach-and-learn process of Physics, for all, without distinction, in a class that has students with Intellectual Disability? It was developed in three high schools of the regular teaching network, in classrooms in which students with Intellectual Disability were present. It was based on legal documents and contributions from the inclusive education theorists. It acquired a qualitative character as result of the subjectivity that established in the relations among the subjects that coexist in the same school environment. The research methodology required the immersion in the school environment and the use of techniques such as interviews with teachers, observations in the classroom and application of questionnaires. In the examination of the transcription of the interviews, procedures based on content analysis were used, and for the observations, questionnaires, field diaries and classroom materials used by the teachers, the inductive-deductive method was applied. The results of each of the techniques employed allowed the identification of categories of analysis, which were compared and served as parameters in the elaboration of the proposal of a Physics teaching methodology that is intended to be applicable to all students, including those with Intellectual Disability. The implementation of this proposal was carried out by two physics teachers in the classes of the schools researched and consisted of three stages: the organization of the actions, which had the participation of the researcher and the two teachers; the implementation itself, at which time observations and monitoring of the application of the procedures were made; was concluded with an interview with the teachers and the record of the students' opinions. The results of this procedure are presented as indicative of the validity of the proposal.